A study on slope instability above Chapman's Peak Drive, Cape Peninsula, South Africa - Scott, Duncan George James (Department of Environmental and Geographical Science, 2024)
[page iv ] Chapman's Peak Drive was constructed along a natural unconformity below Chapman's Peak, a suite of slopes that rise directly from the ocean to their summit. A seemingly increased frequency of rockfalls and the death of a young woman in December 1999 led to the closing of the Drive as a public thoroughfare. At the beginning of the year 2000 Chapman's Peak Drive featured in both local and international media because of the wildfires that swept through this area and large portions of the rest of the Cape Peninsula. This led to a heightened public awareness of the obvious physical danger to traffic on Chapman's Peak Drive. This problem of a rockfall activity onto Chapman's Peak Drive is not a new, or unexpected, one as all roads constructed within mountainous terrain will inevitably experience some sort of mass movement of slope material onto their surface at some stage.